Chemistry a molecular approach - Tro, Nivaldo J. (Always learning, 2017)
The Fourth Edition of Niva Tro's Chemistry: A Molecular Approach reinforces students' development of 21st century skills including data interpretation and analysis, problem solving and quantitative reasoning, applying conceptual understanding to new situations and peer-to-peer collaboration. Nivaldo Tro presents chemistry visually through multi-level images-macroscopic, molecular, and symbolic representations-helping students see the connections between the world they see around them (macroscopic), the atoms and molecules that compose the world (molecular), and the formulas they write down on paper (symbolic). The benefits of Dr. Tro's problem-solving approach are reinforced through digital, Interactive Worked Examples that provide students with an office-hour type of environment and expanded coverage on the latest developments in chemistry. New Key Concept Videos explain difficult concepts while new end-of-chapter problems including Group Work questions and Data Interpretation and Analysis questions engage students in applying their understanding of chemistry. The revision has been constructed to easily incorporate material for instructors and students to engage in Before, During, and After class activities."